Development of glycine-copper(ii) hydroxide nanoparticles with improved biosafety for sustainable plant disease management. Issue 36 (3rd June 2020) - Dong, Hongqiang; Xiong, Renci; Liang, You; Tang, Gang; Yang, Jiale; Tang, Jingyue; Niu, Junfan; Gao, Yunhao; Zhou, Zhiyuan; Cao, Yongsong
Abstract : The prepared Gly-Cu(OH)2 NPs could significantly reduce the severity of bacterial black rot and had no effect on phytotoxicity. Abstract : Cabbage black rot caused by Xanthomonas campestris pv. campestris (Xcc) leads to decrease of the production of up to 70%. Copper biocides are widely used to control this disease because of their low-cost application and broad-spectrum antimicrobial activities. Extensive spraying of traditional copper biocides would cause undesirable effects on plants and the environment. In this work, a novel copper-based microbicide was prepared by binding copper with glycine in sodium hydroxide solution (Gly-Cu(OH)2 NPs) and characterized by inductively coupled plasma atomic emission spectroscopy, high-resolution transmission electron microscopy, Fourier transformation infrared spectroscopy, and dynamic light scattering. The results showed that the prepared Gly-Cu(OH)2 NPs had a mean diameter of 240 nm with copper content more than 25.0% and their antimicrobial efficacies against Xcc were significantly better than Kocide 3000 at 400–800 mg L −1 of copper after spraying for 14 days. The phytotoxicity tests under greenhouse conditions showed that Gly-Cu(OH)2 NPs were safer to plants than Kocide 3000 and obviously promoted the growth of plants, which led to the increase of fresh weights of Chinese cabbage and tomato seedlings by 6.34% and 3.88% respectively at a concentration of 800 mg L −1 of copper. As a novel copper-based microbicide, the Gly-Cu(OH)2 NPs can improve effective utilization of copper-based bactericides and reduce phytotoxicity to plants and would be a potential alternative for sustainable plant disease management.